Moral reasoning, whistleblowing intention, and audit judgement moderate the effect of ethical sensitivity on internal audit quality - Badera, I Dewa Nyoman; Jati , I Ketut (International research journal of management, IT and social sciences, 2020)
Empirical research reveals the effect of ethical sensitivity on internal audit quality but it is not always linear because of the role of several contingency factors. The purpose of this study was to determine the effect of ethical sensitivity on internal audit quality. Meanwhile, the specific objective of this research is to determine the ability of contingency factors, such as: moral reasoning, whistleblowing intention, audit judgment moderates the effect of ethical sensitivity on the quality of internal audit. The study population was the internal auditor of PT Bank BUMN "X" Kanwil Bali-Nusra, then the research sample was determined using the saturated sample method. Furthermore, the collected data were tabulated and analyzed using the Moderated Regression Analysis (MRA) technique. The results of this study reveal that: (1) Ethical sensitivity has a positive and significant effect on internal audit quality. (2) Moral reasoning strengthens the positive effect of ethical sensitivity on internal audit quality. (3) Whistleblowing intention strengthens the positive effect of ethical sensitivity on internal audit quality. (4) Audit judgment strengthens the positive effect of ethical sensitivity on internal audit quality.